2011
DOI: 10.1371/journal.pone.0028274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Anthrax Cases Associated with Recreational Use of Animal Hides and Yarn in the United States

Abstract: To determine potential links between the clinical isolate to animal products and their geographic origin, we genotyped (MLVA-8, MVLA-15, and canSNP analysis) 80 environmental and 12 clinical isolates and 2 clinical specimens from five cases of anthrax (California in 1976 [n = 1], New York in 2006 [n = 1], Connecticut in 2007 [n = 2], and New Hampshire in 2009[n = 1]) resulting from recreational handling of animal products. For the California case, four clinical isolates were identified as MLVA-8 genotype (GT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 7 publications
1
40
0
Order By: Relevance
“…The HRM analysis showed that all the strains belong to the subgroup A.Br.008/011 [16]. The MLVA test at 15 loci showed three different genotypes: Albania GT/1, Albania GT/2 and Albania GT/3 ( Figure 2 and Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…The HRM analysis showed that all the strains belong to the subgroup A.Br.008/011 [16]. The MLVA test at 15 loci showed three different genotypes: Albania GT/1, Albania GT/2 and Albania GT/3 ( Figure 2 and Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…Nine novel DNA signatures were selected and developed into SNP discrimination assays. Combined with previously established canSNPs [10]- [12] [24], the set of 27 markers described here allows a more precise and reliable phylogenetically assignment of any B. anthracis strain into 20 sub-lineages or sub-groups. The present method will contribute to improve our ability to characterize B. anthracis strains and to react rapidly when the identity and origin of a suspicious strain need to be established.…”
Section: Discussionmentioning
confidence: 99%
“…MLVA has been used in epidemiological studies of Brucella species (9,10), Streptococcus agalactiae (11), Pseudomonas aeruginosa (12), Bacillus anthracis (13,14), and Salmonella typhimurium (15,16). The discriminatory power of the assay has been increased by the inclusion of more markers.…”
mentioning
confidence: 99%